Abenteuer in Afrika: Variation eines ethno-linguistischen Dissertationsthemas - Monz, Katharina (AAeO - Afrikanistik-Aegyptologie-Online, 2024)
This article presents a summary translation from French of a central theme of my doctoral thesis [Mots croisés de la mobilité – paroles d’aventure et de voyage], which dealt with various aspects of international mobility in West Africa. The following section takes a closer look at the concept of aventure, ‘adventure,’ which is particularly well known in the greater Mali region, and presents it based on the accounts of its participants. In order to broaden the perspective, I will supplement the observations from my dissertation project with a further link between the main terms aventure, adventure, and (West) Africa. The aim of this brief description of how the two terms are linked outside of academic research is to examine whether terms used in research are suitable for everyday use. If the way we use the term aventure in research on migration practices is compatible with how it is understood and used in other contexts, this opens up new opportunities for us to disseminate the results of our research and put them up for discussion. This is particularly valuable when this research deals with different aspects of international migration, as the cross-border movement of people is one of the major core issues of current public and political interest.